2022
DOI: 10.3389/fneur.2022.855362
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture of Baihui and Shenting ameliorates cognitive deficits via Pten/Akt pathway in a rat cerebral ischemia injury model

Abstract: Cerebral ischemic stroke is a huge threat to the health and life of many people. Electroacupuncture (EA) at Baihui (GV20) and Shenting (GV24) acupoints can notably alleviate cerebral ischemia/reperfusion injury (CIRI). However, the molecular basis underlying the effectiveness of EA at the GV20 and GV24 acupoints for CIRI remains largely unknown. Our present study demonstrated that EA treatment at the GV20 and GV24 acupoints markedly alleviated middle cerebral artery occlusion/reperfusion (MCAO/R)-induced cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Chi et al 2018 [56] Neuroprotection GV 20 and GV 14 Post MA/EA 2/15 Hz 1 mA 2 mm/5mm 30 min Su et al 2022 [57] Neuroprotection GV 20 and GV 24 Post EA 1/20 Hz 1-3 mA 2 mm 30 min Sun et al 2019 [58] Neuroprotection GB 34 Post MA NR NR 4-5 mm 30 min Shi et al 2017 [59] Angiogenesis GV 26 Post EA 15 Hz 1 mA 2 mm 5 min…”
Section: Study Mechanism Acupointmentioning
confidence: 99%
See 1 more Smart Citation
“…Chi et al 2018 [56] Neuroprotection GV 20 and GV 14 Post MA/EA 2/15 Hz 1 mA 2 mm/5mm 30 min Su et al 2022 [57] Neuroprotection GV 20 and GV 24 Post EA 1/20 Hz 1-3 mA 2 mm 30 min Sun et al 2019 [58] Neuroprotection GB 34 Post MA NR NR 4-5 mm 30 min Shi et al 2017 [59] Angiogenesis GV 26 Post EA 15 Hz 1 mA 2 mm 5 min…”
Section: Study Mechanism Acupointmentioning
confidence: 99%
“…Therefore, future studies are needed to explore the mechanism by which acupuncture induces this change [58] . In addition, some studies have found that EA may have a neuroprotective effect after cerebral infarction through protein interaction analysis, such as that of phosphate and tension homology deleted on chromosome ten (PTEN)/protein kinase B (Akt) pathway-related protein [57] and phosphatidylinositol 3-kinase (PI3K)/Akt pathway-related protein [69] . Dai et al [55] reported that acupuncture reduced cerebral I/R injury in MCAO rats by regulating adenosine A1 receptors and confirmed that the changes in ATP and adenosine levels were synchronized with the improvement of neurological function and infarct size in MCAO rats.…”
Section: From the Exploration Of Mechanismsmentioning
confidence: 99%
“…Recently, researchers have been actively investigating reliable biomarkers for IS, which can help identify effective targets and mechanisms for acupuncture treatment of IS. Notably, differential expression of various proteins, including Pak4, Akt3, Efnb2, SerpinG1, complement component I, C3, C4B, and beta-2-glycoprotein I, were observed after acupuncture treatment for IS [ 108 , 109 ]. In particular, Pak4, Akt3, and Efnb2 are considered to be important neuroprotective factors [ [110] , [111] , [112] ].…”
Section: Application Of Proteomics In Acupuncture Researchmentioning
confidence: 99%
“…IBS-D was related to processes such as energy metabolism and muscle excitation/contraction, and acupuncture could reverse the impaired normal energy metabolism. [ 108 ] Enteritis EA ST36 30min, 2/week, 3weeks New Zealand white rabbits; The PVS on the cecum TMT; LC-MS/MS; WB validation 110 DEPs (65 ↑, 45 ↓) 1. EA could relieve bleeding, ulcers, adhesions and thickening of the intestinal wall of enteritis and regulate the inflammatory process.…”
Section: Application Of Proteomics In Acupuncture Researchmentioning
confidence: 99%
“…Since no effective treatment for DCI is available, currently, mainly based on hypoglycemic drugs, a new treatment strategy is urgently needed. On the basis of our previous study and the aetiology of DCI, we propose a new treatment method, “Adjust Zang Arouse Spirit” electroacupuncture”, where Baihui (GV20) and Shenting (GV24) are essential acupuncture points for treating mental disorders ( 15 ). This study was designed to prove the effectiveness of the “Adjust Zang Arouse Spirit” electroacupuncture treatment for DCI and to explore its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%